Students’ Perception of Using Animated Videos in Teaching Writing Recount Text of 8 Graders at SMP N 7 Padang - Putri, Eritna Bernandes; Ayudhia, Honesty Yonanda (Journal of English Language Teaching, 2025)
This study aims to find out the perceptions of eighth-grade students regarding the use of animated videos in teaching writing recount texts at SMPN 7 Padang. Recognizing the challenges students often face in generating ideas, organizing thoughts, and structuring their writing when creating recount text, this research explores animated videos as an innovative pedagogical tool. Utilizing a quantitative research design, the study involved 62 students from two purposively selected classes (VIII.7 and VIII.8) who had prior experience with animated videos in their writing instruction. Data were collected using a 40-item questionnaire, structured around four key indicators: engagement, preference, practicality, and impact on writing skills. The findings reveal a predominantly positive perception among students towards the integration of animated videos. The overall mean score for student perception was 3.03, falling within the "Positive" category. Specifically, animated videos were highly perceived as engaging, with an average score of 3.07, indicating increased student interest and motivation. Students also showed a strong preference for animated videos over traditional methods (mean score 3.03), particularly when the videos were interactive and illustrative. Furthermore, the practicality of animated videos in simplifying complex concepts and visualizing text structures was acknowledged (mean score 2.99). Most significantly, students perceived a positive impact on their writing skills (mean score 3.04), noting improvements in creativity, organization, and overall clarity in their recount texts. These results suggest that animated videos serve as effective supplementary tools, enhancing both the learning experience and writing outcomes in English language instruction.